STATISTICAL TECHNIQUES APPLIED IN THREE JOURNALS OF AGRICULTURAL SCIENCES WITH A FOCUS ON ANIMAL SCIENCE - BUSANELLO, Marcos; ANDRADE, Thiago Sergio de; AROEIRA, Carolina Naves; DIAS, Carlos Tadeu dos Santos (Brazilian Journal of Biometrics, 2018)
There are few previous studies that investigate the most used statistical techniques in animal science. Due to the large number of tools and methods available for statistical analysis, it is important to identify the most applied ones for this area of research. Therefore, we aimed to identify the use of different statistical techniques (designs, software and analysis) used in two Brazilian journals (Ciência Rural and Revista Brasileira de Zootecnia) and one international journal (Journal of Animal Science). In order to do this, scientific articles published during the years 2011 to 2015 were selected to form a database. Our article discusses the use of designs, software and analyses most commonly used in the journals studied. To study this, we used descriptive statistics and multivariate approaches. Completely randomized and randomized blocks design were the principal designs used in animal science. The SAS® software was the principal software used. Finally, analysis of variance was the principal statistical method, followed by regression analysis. There were no differences between the journals over time regarding the use of statistical analyses. The results highlight the importance of hypothesis testing within animal science.